Analisis Gaya Bahasa Pembelajar Bahasa Arab sebagai Bahasa Asing: Studi Kasus pada Alumni Pesantren dan Non Pesantren - Fitria Fitria; Indah Rahmayanti; Farroha Firmaningrum; Syaiful Mustofa (Mantiqu Tayr: Journal of Arabic Language, 2024)
Language plays an essential role for human interactions and communication and it can also show cultural, social and individual identity. Ones’ background may generate different language use in either written or spoken contexts. Against this backdrop, this research aims to explore the written language styles of Islamic boarding school and non-Islamic boarding school alumni who learn Arabic as a foreign language. This research is designed under qualitative perspective and employs a case study approach. Data was in the form of documents, obtained through informant essays about the experience of learning Arabic. Besides, the data was also collected through semi-structured interviews with two informants to further understand differences in educational background, differences in first language, family background, foreign language mastered, and exposure to Arabic. Data was analysed by reading essays then providing coding and categorization, which was carried out separately by each researchers, conducting discussions on written language styles focusing on the choice of language used from a sociolinguistic aspect. The results of this research demonstrate that the written language styles of students of Arabic as a foreign language between Islamic boarding school and non-Islamic boarding school alumni have differences in terms of lexical choice, phrases and sentence structure.  Such differences happen because of the way a learner's family background, foreign language mastery, and exposure to Arabic influence the written language style. Moreover, the findings have demonstrated how different academic background, language exposure, and learning impact to one’s language style. Given the limited number of the informant, future research may consider recruiting more diverse and more participants.